Mondialisation and the immanent critical potential of food: Luc Moullet's Genèse d'un repas (1978). (August 2014) - Cruickshank, Ruth
Mobilising the immanent critical potential of food as well as of Derrida's deconstruction of mondialisation with its interruption of totalising understandings of globalisation, this article re-examines Luc Moullet's 1978 documentary Genèse d'un repas which follows how tuna from Senegal, eggs from Amiens and Ecuadorian bananas reach French plates. Eurocentric Marxist and post-Marxist analyses of these economic flows are bought at once into focus and into question. The analysis uncovers imbricated histories of European exploitation (the slave trade, colonialism, la Françafrique). Commercial (Banania) and literary intertexts (Senghor and Fanon) evoked by misleading branding reveal a world of European racism still in process. Although self-reflexive, Moullet's filmmaking is also open to critical interruption. Nonetheless, the film emerges as an immanent critique of the specificities of historical and evolving power relations of both filmmaking and the historical, cultural and economic processes of the Eurocentric food industry, interrupting the universalising dynamics of globalisation.